Effect of topical rosemary essential oil on Raynaud phenomenon in systemic sclerosis. (October 2018) - von Schoen-Angerer, Tido; Deckers, Bernhard; Henes, Jörg; Helmert, Eduard; Vagedes, Jan
Highlights: Existing treatments for Raynaud's phenomenon in systemic sclerosis are unsatisfactory. Topical application of Rosamarinus officinalis oil had warming effect in a woman with systemic sclerosis and Raynaud. Thermography is useful for assessing hand circulation problems in systemic sclerosis and to demonstrate treatment effects. Abstract: Introduction: Raynaud's phenomenon is the earliest manifestation of systemic sclerosis. Nitroglycerin gel is the only proven topical therapy. Methods: A 53-year-old woman with systemic sclerosis had topical Rosamarinus officinalis (rosemary) oil, often used in anthroposophic medicine, applied to her hands over 3 days and then, separately, olive oil. Results: Thermography images showed significant warming of fingers after rosemary oil, but not after olive oil, coinciding with the patient's subjective experience. Conclusions: Topical Rosamarinus officinalis oil had a vasodilator and warming effect in a patient with systemic sclerosis and Raynaud's phenomenon.